Ruth Crawford’s String Quartet, Mvt. 3: An Analysis of Dynamic Counterpoint, Contour Similarity, and Musical Form - Wu, Yi-Cheng (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
In the third movement of her String Quartet, locally Ruth Crawford crafts a unique dynamic contrapuntal fabric, where each instrument plays a different alternation of crescendo and diminuendo, thus the same dynamics never synchronize. Globally, this dynamic contrapuntal texture projects an extensively long gradual sound expansion from ppp to fff. In addition, Crawford stresses two temporary dynamics f and fff, subtly dividing the form into three parts. To support Crawford’s subtle formal division, I translate Crawford’s dynamic counterpoint into a chronological sequence of verticalized contours and measure their similarity. I find the essential changes in contour similarity always coincide with the structural boundary, sharpening the formal division in Crawford’s schematic design.